2007
DOI: 10.2151/jmsj.85.733
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Precipitable Water Derived from Ground-Based GPS Measurements with Radiosonde Observations over the Korean Peninsula

Abstract: Precipitable water (PW) obtained from a permanent ground-based Global Positioning System (GPS) network on the Korean Peninsula was evaluated by using radiosonde measurements for two years. The GPS-derived PW is also validated using 5-min and 2-hourly troposphere products from International GNSS Service (IGS).The GPS-derived PW from our analysis and the IGS products were reasonably consistent with mean bias (Ours minus IGS products) of À0.27 mm and a standard deviation of 0.78 mm.The PW derived from radiosonde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
2
12
0
3
Order By: Relevance
“…It was also shown that the dry bias of radiosonde was greatly affected by the solar radiation (Wang et al 2002) and the main factors of the radiosonde bias were relative humidity in the atmosphere and the solar radiation depending on the elevation (Wang & Zhang 2008). In addition, Kwon et al (2007) showed that a radiosonde observation had a dry bias compared to a GPS observation and the PWV difference between those two observations increased especially in daytime.…”
Section: Introductionmentioning
confidence: 96%
“…It was also shown that the dry bias of radiosonde was greatly affected by the solar radiation (Wang et al 2002) and the main factors of the radiosonde bias were relative humidity in the atmosphere and the solar radiation depending on the elevation (Wang & Zhang 2008). In addition, Kwon et al (2007) showed that a radiosonde observation had a dry bias compared to a GPS observation and the PWV difference between those two observations increased especially in daytime.…”
Section: Introductionmentioning
confidence: 96%
“…The observation values of radiosonde which has been used for the longest period of time are used often for verification, calibration and analysis of characteristics for values measured by other systems. For example, in a relative comparison with values measured by MWR, average difference from radiosonde results was represented as 1-5 mm, and standard deviation was represented as 1-2 mm (Westwater et al 1989, Liou et al 2001, Basili et al 2002, Pacione et al 2002, and in a relative comparison with values measured by GPS, average difference from radiosonde results was represented as 1-4 mm, and standard deviation was represented as 1-5 mm (Moon et al 1999, Kwon et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…기존의 라디오존데 오차 및 편차 비교 실험연구 결 과를 보면 습도의 경우 Global Positioning System (GPS) 가강수량과 비교했을 때 과소 측정(건조 편차) 하는 경향이 있는 데 (Wang et al, 2002;Turner et al, 2003;Nakamura et al, 2004;Wang and Zhang, 2008), 이는 수치모델의 가강수량을 과소 모의할 수 있다 (Lorence et al, 1996). 이러한 상대습도의 과소 관측 경향은 외국에 비해 활발하게 수행된 편은 아니 지만 국내 일부 연구결과에서도 확인된 바 있다 (Kwon et al, 2007;Kim et al, 2009 (1)…”
Section: )unclassified